OPTIMALISASI POLA TANAM LAHAN KERING PADA KAWASAN EKONOMI MASYARAKAT (KEM) DI KECAMATAN KAYANGAN KABUPATEN LOMBOK UTARA - Fadli, Fadli; Suwardji, Suwardji (Agros Journal of Agriculture Science, 2024)
The aim of this research ware: (1) Analyzing the income from each farming pattern of the Community Economic Area in Gumantar Village, Kayangan District, North Lombok Regency; (2) Analyzing the planting pattern of the Community Economic Area in a year that maximizes profits; (3) Knowing the problems of Community Economic Area farmers in carrying out crop farming, both technical cultivation, economic, and institutional issues. The method used in this study is a descriptive method, while the data collection process is carried out using survey techniques. The results of the study ware: (1). The highest amount of income obtained by farmers with a planting pattern was (Melon-Tomato-Chili) of Rp. 243,497,507 per Ha, and the lowest with a planting pattern (Corn-Bero-Bero) of Rp. 8,750,325 per Ha. (2). The optimal planting pattern in the Community Economic Area is Melon-Tomato-Chili, and (3). The problems faced by farmers are the use of irrigation water that was difficult to anough of the land area, technical plant cultivation includes: pests and diseases, the availability of production facilities, seeds, and subsidized fertilizers that are not evenly distributed.